Long jump mechanics - olympic versus paralympic champion - Funken, J.; Willwacher, S.; Heinrich, K.; Müller, R.; Hobara, H.; Grabowski, A. M.; Brüggemann, G. P.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2017)
In the last 20 years the long jump world record of athletes with an amputation of the lower extremities has improved by over two meters. However, there is no recent research on amputee long jumping and no information about amputee long jump kinetics. In this study the take-off step of an Olympic and a Paralympic champion were analyzed with regard to jumping mechanics. A 3D motion capturing system (Vicon) and a force plate (Kistler) were used to capture kinematic and kinetic data. Inverse dynamic calculations (Dynamicus, Alaska) revealed remarkable differences with respect to mechanical loading and motor solutions between the transtibial amputee and non-amputee long jumper. Mechanical constraints and material properties of the prosthesis might influence the kinematic chain of the amputee athlete and impose the need for an alternative motor solution.